War As Entertainment and Contents Tourism in Japan. - Yamamura, Takayoshi. (Routledge Focus on Asia Series, 2022)
This book examines the phenomenon of war-related contents tourism throughout Japanese history, from conflicts described in ancient Japanese myth through to contemporary depictions of fantasy and futuristic warfare.